Caregiver alignment with triage acuity levels and drivers for discrepancy between caregiver assessment and triage acuity levels: a cross-sectional questionnaire based study - Noelie Lengeler; Carl Alessandro Starvaggi; Manon Jaboyedoff; Sophie Affentranger; Kristina Keitel (BMC Health Services Research)
Abstract Background Caregiver concern is the main driver to paediatric emergency departments visits. Understanding caregiver worries is crucial to guide patients to the most appropriate healthcare setting. Previous research shows mixed findings on the accordance between caregiver assessment and professional triage. Methods We assessed data from two questionnaire-based studies conducted over 27 months in two tertiary paediatric emergency departments in Switzerland to compare caregiver perception of their child’s medical acuity and standard nurse triage. Furthermore, we examined socioeconomic factors associated with caregiver perception. Results Our study of 2,126 children seen in the two paediatric emergency departments showed that caregiver assessment aligned well with the acuity assigned by professional triage in 89% (1,901/2,126) of cases. In 142 cases (7%, 142/2,126), caregivers rating their child’s severity higher than nurse’s triage while in 83 cases (4%, 83/2,126), they rated it lower. In an univariable analysis, we found that family’s difficulties paying bills (20% vs. 12%) and low maternal education (19% vs. 10%) were associated with a higher percentage of caregiver rating their child’s severity higher than nurse’s triage. Fever as the main complaint was associated with caregiver rating their child’s severity lower than nurse’s triage. Conclusions This questionnaire-based study shows that caregiver’s assessment of the severity of the child and nurse triage are concordant in most situations. Our study sheds light on the association between caregiver assessment and professional triage in two paediatric emergency departments in Switzerland, revealing some of the factors leading to discordance. These factors most probably reflect health illiteracy. It is important that healthcare professionals recognize and address factors influencing caregiver assessments to facilitate accurate decision-making and enhanced paediatric emergency care outcomes.